State of clinical pain research in Nepal: a systematic scoping review. (November 2019) - Sharma, Saurab; Jensen, Mark P.; Pathak, Anupa; Sharma, Sweekriti; Pokharel, Mukesh; Abbott, J. Haxby
Abstract : Abstract: Before determining the pain research priorities for a country, a comprehensive literature review of existing research is warranted. We aimed to (1) identify and describe the extent and nature of pain research performed in Nepal, (2) identify existing knowledge and significant knowledge gaps, and (3) provide recommendations for future studies. We conducted a systematic scoping review of the literature, in accordance with recommended guidelines. We searched local and international databases to identify research conducted in Nepal on individuals with a diagnosis of clinical pain conditions. A pair of independent reviewers screened the studies for inclusion. We identified 1396 records and included 116 studies. Most studies were published in Nepalese journals (75%) and were conducted in clinical settings (73%). Postsurgical pain was the most commonly studied pain condition (33%), followed by musculoskeletal pain (16%), headache (14%), and low back pain (13%). The most common research topics, in order of frequency, were (1) medical management (40%), (2) pain prevalence/incidence (21%), (3) diagnostic procedures (15%), (4) surgical management (8%), and (5) patient-reported outcome measurement (8%). Research gaps and potential areas of research waste were identified. Although a large number of research articles about pain in Nepal have been published, the majority of these have focused on the biomedical diagnosis and management of pain. Other topic areas (eg, psychological and social aspects of pain) are under-represented. The findings may inform future research directions for maximizing the knowledge that could be gained. Abstract : Supplemental Digital Content is Available in the Text.